Virtual Tour Univeristas Bina Darma Berbasis Android - Muhammad Soekarno Putra; Hamim Tezar Rizandi (Jurnal Pengembangan Sistem Informasi dan Informatika, 2022)
Bina Darma University is one of the private universities located in the city of Palembang. In providing information about the institution, Bina Darma University has used several methods, including websites, brochures, TV streaming, radio and social media such as Instagram and Facebok. However, from several existing media, it turns out that it still doesn't provide information about the location of the room and also the places around the campus. In this case, researchers are interested in making an information media application to introduce the area around the campus by using virtual tour technology with Android-based mobile technology with an offline system so that it will be easier, because it can be accessed using smartphones or other android-based gadgets without a connection. Internet. The applications used in the manufacture of Andoid applications are Unity 3D. The development method used in building this virtual tour application of the MDLC (Multimedia Development Life Cycle). Keywords: Virtual Tour, Unity 3D, Mobile, Android, MDLC